Health-Related Quality of Life, Cachexia and Overall Survival After Major Upper Abdominal Surgery: A Prospective Cohort Study. (March 2017) - Aahlin, E. K.; Tranø, G.; Johns, N.; Horn, A.; Søreide, J. A.; Fearon, K. C.; Revhaug, A.; Lassen, K.
Background and Aims: Major upper abdominal surgery is often associated with reduced health-related quality of life and reduced survival. Patients with upper abdominal malignancies often suffer from cachexia, represented by preoperative weight loss and sarcopenia (low skeletal muscle mass) and this might affect both health-related quality of life and survival. We aimed to investigate how health-related quality of life is affected by cachexia and how health-related quality of life relates to long-term survival after major upper abdominal surgery. Materials and Methods: From 2001 to 2006, 447 patients were included in a Norwegian multicenter randomized controlled trial in major upper abdominal surgery. In this study, six years later, these patients were analyzed as a single prospective cohort and survival data were retrieved from the National Population Registry. Cachexia was derived from patient-reported preoperative weight loss and sarcopenia as assessed from computed tomography images taken within three months preoperatively. In the original trial, self-reported health-related quality of life was assessed preoperatively at trial enrollment and eight weeks postoperatively with the health-related quality of life questionnaire Short Form 36. Results: A majority of the patients experienced improved mental health-related quality of life and, to a lesser extent, deteriorated physical health-related quality of life following surgery. There was a significant association between preoperative weight loss and reduced physical health-related quality of life. No association between sarcopenia and health-related quality of life was observed. Overall survival was significantly associated with physical health-related quality of life both pre- and postoperatively, and with postoperative mental health-related quality of life. The association between health-related quality of life and survival was particularly strong for postoperative physical health-related quality of life. Conclusion: Postoperative physical health-related quality of life strongly correlates with overall survival after major upper abdominal surgery.